Activité antifongique de l’extrait de l’huile essentielle de Salvia officinalis sur les deux séquences biologique de fusariume.sp, Agent de la fusariose des agrumes - Cheltite, Aaissam eddin; Ouaghi, Sidahamed (My University, 2023)
With the aim of finding natural molecules with a fungicidal effect, this study focused on the antifungal activity of the essential oil of an aromatic and medicinal plant Salvia officinalis. Salvia officinalis is a medicinal and aromatic plant in the Lamiaceae family. The essential oil was extracted by hydrodistillation, giving a yield of 0.45%. The results of an in vitro test on the effect of Salvia officinalis leave on mycelial growth and sporulation (Fusarium sp). The results obtained show that the reduction in mycelial growth synchronizes with the increase in the concentration of the essential oil, the higher the concentration, the greater the inhibitory effect.
Keywords: Fusarium sp; Salvia officinalis; croissance mycélienne; sporulation; huile essentielle